Immunohistochemical Evaluation of Cytokeratin 17 Expression in Oral Squamous Cell Carcinoma : Life Sciences- Pathology - Gyanchandani, Dr. Ankita; Shukla, Dr. Samarth; Dr. RavindraKadu (International Journal of Life Science and Pharma Research, 2023)
Oral squamous cell carcinoma (OSCC), which makes up 80–90% of all malignant neoplasms of the mouth, is the mostcommon type of oral cancer. Immunohistochemistry plays a crucial role in diagnostic pathology by aiding in identifying andclassifying tumors IHC is utilized to study the distribution and localization of specific proteins. Identifying diagnostic markers forOSCC is essential for early diagnosis and patient-specific treatment. Cytokeratins (CK) are a family of intermediate filamentspredominantly expressed in epithelial cells. The study aimed to evaluate immunohistochemical expression cytokeratin 17 in 50cases of microscopically confirmed OSCC. The present study was observational, with retrospective and prospective sampling.The study was carried out for two years, from 2020 to 2022. The present study was designed to determine CK 17 expressionby IHC and to correlate CK 17 expression with Broders grading of OSCC and other clinical pathologic parameters.Immunostaining for CK 17 was performed. The statistical analysis was done by chi-square test. In this study, there was asignificant correlation between CK 17 expression and Broders grading, and CK 17, when correlated with other clinic pathologicparameters, showed no significant correlation. It was concluded that Cytokeratin17 expression could correlate with theBroders’ Grading, thus contributing to early detection and more accurate determination of tumor aggressiveness to determineappropriate therapy.